BRANDING AND DIGITAL MARKETING STRATEGIES FOR SMES IN BRIDGING THE MARKET GAP BETWEEN URBAN AND RURAL AREAS - Suslinawati; Hadenan Towpek; Ignatius Septo Pramesworo (CV. Adiba Aisha Amira, 2026)
This study examines branding and digital marketing strategies as effective solutions for Micro, Small and Medium Enterprises (MSMEs) in bridging the market gap between urban and rural areas. Through a literature review, it was found that strengthening brand identity based on local wisdom, authentic storytelling and attractive visual packaging can enhance the competitiveness of rural MSME products in competitive urban markets. These branding strategies create unique differentiation through a unique selling proposition (USP) rooted in local cultural values and natural resources, building consumer trust and long-term loyalty. Meanwhile, digital marketing via social media (Instagram, TikTok), marketplaces (Shopee, Tokopedia), and simple data analytics enables MSMEs to overcome physical infrastructure limitations by gaining real-time access to the national market. The integration of local-modern content strategies, collaboration with local influencers, and the optimisation of digital payment methods such as QRIS have been shown to increase turnover by up to 300% for businesses in remote areas. The synergy between strong branding and digital distribution creates an inclusive ecosystem that empowers the rural economy. Research findings confirm that holistic digital transformation—supported by digital literacy, internet infrastructure, and stakeholder collaboration—not only reduces regional disparities but also contributes to the Sustainable Development Goals (SDGs) through economic equality and the preservation of local culture. Recommendations include mass training programmes, subsidies for rural digital access, and certification of local products to accelerate the national adoption of these strategies.